Dye-based fluorescent organic nanoparticles made from polar and polarizable chromophores for bioimaging purposes: a bottom-up approach - Daniel, Jonathan; Dal Pra, Ophélie; Kurek, Eleonore; Grazon, Chloé; Blanchard-Desce, Mireille (Comptes Rendus. Chimie)
In the last decades, inorganic nanoparticles have attracted growing attention in the field of nanophotonics, especially for bioimaging purposes. Among them luminescent metal-, semiconductor- or oxide-based “hard” nanoparticles have been the most widely used. Yet, they raise concern with respect to toxicity and degradability issues. In that context, we have developed innovative bottom-up approaches towards ultrabright dye-based fluorescent organic nanoparticles (dFONs). Our strategy is based on the design and synthesis of custom-designed (multi)polar and polarizable dyes (PPDs) as building blocks of dFONs. These nanoparticles are readily prepared using expeditious and green protocols involving nanoprecipitation of the hydrophobic dyes in water. Their luminescence can be tuned in the whole visible region down to the Near Infra-Red I (NIR-I) region while their nonlinear optical responses can be enhanced thanks to cooperative effects. Intriguingly, the implemented strategy also enables modulating and improving the dFONs colloidal and structural stability as well as their photostability. As a result, dFONs made from PPDs that combine unprecedented brightness (up to 108 M-1·cm-1 and 106 GM), remarkable colloidal stability and absence of toxicity, have been elaborated, providing superior substitutes to Quantum Dots. Such dFONs can be used as ultrasensitive contrast agents for in vivo two-photon angiography in small animals, while hyper-bright NIR-emitting FONs, that show remarkable photostability and excellent biocompatibility, can be successfully imaged and tracked at the single particle level in water. Furthermore, ultrabright dFONs of different colors that internalize into cells can be tracked within living cells allowing real-time multicolor single particles tracking. In contrast, stealth emitters are required for tracking cell-surface receptors or exploring the extracellular space. In this direction, spontaneously stealth, size-tunable, ultrabright and red to NIR emitting dFONs were developed. Thanks to these unique properties, these dFONs could be imaged and tracked up to 150 µm deep in brain tissue.